2020
DOI: 10.1101/2020.05.08.20089268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and outcomes of pregnant women hospitalised with confirmed SARS-CoV-2 infection in the UK: a national cohort study using the UK Obstetric Surveillance System (UKOSS)

Abstract: Objective: To describe a national cohort of pregnant women hospitalised with SARS-CoV-2 infection in the UK, identify factors associated with infection and describe outcomes, including transmission of infection, for mother and infant.Design: Prospective national population-based cohort study using the UK Obstetric Surveillance System (UKOSS). Setting: All 194 obstetric units in the UK Participants: 427 pregnant women admitted to hospital with confirmed Sars-CoV-2 infection between 01/03/2020 and 14/04/2020. 69… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
158
7
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(187 citation statements)
references
References 31 publications
8
158
7
14
Order By: Relevance
“…2 (Table 1), a figure which is 3.4 times higher than the total number of COVID-19-related maternal deaths reported throughout the rest of the world at the time of writing. [3][4][5][6][7] The current mortality rate is 12.7% in the Brazilian obstetric population, which is also higher than rates reported so far in the literature. 3,4,7 Notably, the mortality rate was higher for cases identified in the postpartum period than during pregnancy, likely reflecting the onset timing of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 71%
“…2 (Table 1), a figure which is 3.4 times higher than the total number of COVID-19-related maternal deaths reported throughout the rest of the world at the time of writing. [3][4][5][6][7] The current mortality rate is 12.7% in the Brazilian obstetric population, which is also higher than rates reported so far in the literature. 3,4,7 Notably, the mortality rate was higher for cases identified in the postpartum period than during pregnancy, likely reflecting the onset timing of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 71%
“…Comparability of available data is impaired due to methodological differences in studies. For example, Iran 8 reported critical cases only and denominators differ among other studies, such as mixed‐severity hospitalized cases (UK and France), 4,5 acute respiratory distress syndrome cases (Brazil), 6 and COVID‐19 pregnant women in general (US and Mexico) 3,7 . These preliminary data, however, expose the weaknesses of maternity services in middle‐income countries.…”
Section: Country (First Author Year) Population (2019) Gini Index (Wmentioning
confidence: 88%
“…We searched PubMed/MEDLINE, EMBASE, SciELo and LILACS for documented COVID‐19‐related maternal deaths from December 2019 until July 1, 2020. After removal of duplicates, our results showed that six countries had reported maternal deaths due to COVID‐19 by July 1, 2020: three high‐income countries (France, UK, and US) 3–5 and three middle‐income countries (Brazil, Iran, and Mexico) 6–8 . The total number of reported maternal deaths was 160 (Table 1).…”
Section: Country (First Author Year) Population (2019) Gini Index (Wmentioning
confidence: 91%
See 1 more Smart Citation
“…In the UK, Knight et al . have published interim results from the NIHR‐funded UK Obstetric Surveillance System (UKOSS) study (https://www.npeu.ox.ac.uk/ukoss, http://www.isrctn.com/ISRCTN40092247), which provides reliable data on maternal and neonatal outcomes 2 .…”
mentioning
confidence: 99%